2017
DOI: 10.1021/acs.langmuir.7b02423
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and Colloidal Stabilization of Ca(OH)2 in the Presence of Nopal Juice (Opuntia ficus indica): Implications in Architectural Heritage Conservation

Abstract: Hydrated lime (Ca(OH)) is a vernacular art and building material produced following slaking of CaO in water. If excess water is used, a slurry, called lime putty, forms, which has been the preferred craftsman selection for formulating lime mortars since Roman times. A variety of natural additives were traditionally added to the lime putty to improve its quality. The mucilaginous juice extracted from nopal cladodes has been and still is used as additive incorporated in the slaking water for formulation of lime … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
42
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 58 publications
1
42
0
1
Order By: Relevance
“…9,10 However, there is still a lack of understanding about the interactions between organic materials and inorganic cements. For instance, polysaccharides, fatty acids (olive oil), and Nopal juice (a plant extract) have been used in traditional lime mortars to improve some of their properties 11 but in most cases they displayed a negligible impact on the mechanical strength. 12 Nevertheless, recent research has shown that the presence of organic molecules in chalk (a carbonate sedimentary rock) is key to understand its strength on geological time scales.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 However, there is still a lack of understanding about the interactions between organic materials and inorganic cements. For instance, polysaccharides, fatty acids (olive oil), and Nopal juice (a plant extract) have been used in traditional lime mortars to improve some of their properties 11 but in most cases they displayed a negligible impact on the mechanical strength. 12 Nevertheless, recent research has shown that the presence of organic molecules in chalk (a carbonate sedimentary rock) is key to understand its strength on geological time scales.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the disadvantages of organic materials, inorganic materials have been developed because of their high compatibility and long‐term durability . Ca(OH) 2 is a representative inorganic material used in the conservation of cultural heritage . Compared to bulk particles, nanosized Ca(OH) 2 has good permeability and high reactivity with CO 2 , which can ensure fast carbonation, high carbonation degree, and effective consolidation .…”
Section: Introductionmentioning
confidence: 99%
“…Compared to bulk particles, nanosized Ca(OH) 2 has good permeability and high reactivity with CO 2 , which can ensure fast carbonation, high carbonation degree, and effective consolidation . Therefore, during the last two decades, researchers have developed various methods to obtained nanosized Ca(OH) 2 . However, drawbacks of synthesis methods (high energy, expensive, time‐consuming or complex operations) remain unresolved.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations